Absorption filaments toward the massive clump G0.253+0.016 - Bally, J.; Rathborne, J.; Longmore, S.; Jackson, J.; Alves, J.; Bressert, E.; Contreras, Y.; Foster, J.; Garay, G.; Ginsburg, A.; Johnston, K.; Kruijssen, J.; et al. (Institute of Physics Publishing, 2014)
ALMA HCO+ observations of the infrared dark cloud G0.253+0.016 located in the central molecular zone of the Galaxy are presented. The 89 GHz emission is area-filling, optically thick, and sub-thermally excited. Two types of filaments are seen in absorption against the HCO+ emission. Broad-line absorption filaments (BLAs) have widths of less than a few arcseconds (0.07-0.14 pc), lengths of 30-50 arcsec (1.2-1.8 pc), and absorption profiles extending over a velocity range larger than 20 km s–1. The BLAs are nearly parallel to the nearby G0.18 non-thermal filaments and may trace HCO+ molecules gyrating about highly ordered magnetic fields located in front of G0.253+0.016 or edge-on sheets formed behind supersonic shocks propagating orthogonal to our line of sight in the foreground. Narrow-line absorption filaments (NLAs) have line widths less than 20 km s–1. Some NLAs are also seen in absorption in other species with high optical depth, such as HCN, and occasionally in emission where the background is faint. The NLAs, which also trace low-density, sub-thermally excited HCO+ molecules, are mostly seen on the blueshifted side of the emission from G0.253+0.016. If associated with the surface of G0.253+0.016, the kinematics of the NLAs indicate that the cloud surface is expanding. The decompression of entrained, milli-Gauss magnetic fields may be responsible for the re-expansion of the surface layers of G0.253+0.016 as it recedes from the Galactic center following a close encounter with Sgr A.